Do credit lines provide reliable liquidity insurance? Evidence from commercial-paper backup lines - Niklas Amberg (Sveriges Riksbank, 2023)
Commercial-paper backup lines account for a substantial share of undrawn loan commitments in the corporate sector, but have despite this received scant attention in the credit-line literature. In this paper, I study the liquidity-insurance properties of backup lines using a comprehensive loan- and security-level dataset and the sharp contraction of the Swedish commercial-paper market during the COVID-19 pandemic as an exogenous shock to the supply of market-provided liquidity. I find that backup lines provide commercial-paper issuers with reliable liquidity insurance and that banks' liquidity provision via commercial-paper backup lines in periods of distress does not crowd out lending to other firms.
Keywords: D22; G21; G32; 330; Credit lines; bank lending; liquidity insurance; commercial paper; COVID-19